Sensitivity analysis of an HgCdTe based photovoltaic receiver for long-wavelength free space optical communication systems - Dwivedi A.D.D.; Chakrabarti P. (My University, 2025)
We examine theoretically the performance of an Hg0.77Cd0.23Te based p-n photodetector/HFET optical receiver due to its possible application at 10.6 μm free space optical communication system at high bit rate. A rigorous noise model of the receiver has been developed for this purpose. We calculate the total noise and sensitivity of the receiver. The front-end of the receiver exhibits a sensitivity of -45 dBm at a bit rate of 1 Gb/s and -30 dBm at a bit rate of 10 Gb/s, and the total mean-square noise current = 5 × 10-15 A2 at a bit rate of 1 Gb/s and = 10-12 A2 at a bit rate of 10 Gb/s, and a 3-dB bandwidth of 10 GHz. © Tianjin University of Technology and Springer-Verlag GmbH 2009.